Modeling of a complete proton exchange membrane fuel cell - Tun Win Aung. (2008)
This project concentrates on the development of a complete proton exchange membrane fuel cell model, which could produce useful results for fuel cell design and deciding on the optimal operating conditions of the fuel cell for specific applications. The objective includes developing a complete mathematical model of proton exchange membrane.